Prasugrel 5 mg in the Very Elderly Attenuates Platelet Inhibition But Maintains Noninferiority to Prasugrel 10 mg in Nonelderly Patients: The GENERATIONS Trial, A Pharmacodynamic and Pharmacokinetic Study in Stable Coronary Artery Disease Patients - ERLINGE, David; GURBEL, Paul A; CHUNMEI ZHOU; MOSER, Brian A; JAKUBOWSKI, Joseph A; SMALL, David S; WINTERS, Kenneth J; ANGIOLILLO, Dominick J; JAMES, Stefan; LINDAHL, Tomas L; SVENSSON, Peter; TEN BERG, Jurrien M; et al. (Journal of the American College of Cardiology, 2013)
This study assessed pharmacodynamic (PD) response to the reduced prasugrel maintenance dose of 5 mg in very elderly (VE) patients (≥75 years of age). In the TRITON-TIMI 38 (TRial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet InhibitioN with Prasugrel-Thrombolysis In Myocardial Infarction 38) study prasugrel 10 mg reduced ischemic events versus clopidogrel 75 mg, but increased bleeding in VE patients. We examined PD and active metabolite pharmacokinetics (PKs) with prasugrel 5 and 10 mg and clopidogrel 75 mg in a 3-period (12 days each) blinded, crossover study in VE (n = 73; mean: 79 ± 3 years of age) or (n = 82) nonelderly (NE) (≥45 to <65 years of age; mean: 56 ± 5 years of age) stable coronary artery disease (CAD) patients receiving background aspirin. Assays included light transmission aggregometry (LTA), VerifyNow P2Y12 (VN-P2Y12), and vasodilator-associated stimulated phosphoprotein (VASP). The primary comparison was noninferiority of maximum platelet aggregation (MPA) comparing the median for prasugrel 5 mg in VE versus the 75th percentile for prasugrel 10 mg in NE, using a pre-specified 1-sided 97.5% confidence interval for the difference <15%. Prasugrel 5 mg in VE met the primary PD noninferiority criterion versus prasugrel 10 mg in NE. For prasugrel 5 mg, MPA was significantly lower (57 ± 14%) than clopidogrel (63 ± 14%; p < 0.001) in VE but higher than prasugrel 10 mg in NE (46 ± 12%; p < 0.001). PD response by LTA, VN-P2Y12, and VASP during all treatments appeared similar between age cohorts. Prasugrel 5 mg resulted in fewer VE poor responders than clopidogrel. Rates of mild bleeding were higher with prasugrel 10 mg but similar for prasugrel 5 mg versus clopidogrel 75 mg. In aspirin-treated stable CAD patients, prasugrel 5 mg in VE attenuated platelet inhibition while meeting pre-specified noninferiority criterion versus prasugrel 10 mg in NE, with significantly better PD response and fewer poor responders compared to clopidogrel 75 mg in VE. (Comparison of Prasugrel and Clopidogrel in Very Elderly and Non-Elderly Patients With Stable Coronary Artery Disease [GENERATIONS]; NCT01107912).